2014
DOI: 10.1016/j.apsoil.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Land-use intensification and agroforestry in the Kenyan highland: Impacts on soil microbial community composition and functional capacity

Abstract: 13This study investigates microbial communities in soil from sites under different land use in 14 Kenya. We sampled natural forest, forest plantations, agricultural fields of agroforestry farms, 15agricultural fields with traditional farming and eroded soil on the slopes of Mount Elgon, 16Kenya. We hypothesised that microbial decomposition capacity, biomass and diversity 1) 17 decreases with intensified cultivation; and 2) can be restored by soil and land management in All 31 substrates were metabolised in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 26 publications
4
19
0
2
Order By: Relevance
“…The structure of the SWAT model allows only one plant or crop type per HRU. The most typical systems of agroforestry in the watershed are: (1) intercropping sparsely distributed trees with different crops, (2) trees along the hedges and borders, and (3) woodlots (Lagerlöf et al, 2014;Nyaga et al, 2015). The first two agroforestry systems posed a challenge to be explicitly implemented in SWAT because of the model structure.…”
Section: Simulation Of Agroforestrymentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the SWAT model allows only one plant or crop type per HRU. The most typical systems of agroforestry in the watershed are: (1) intercropping sparsely distributed trees with different crops, (2) trees along the hedges and borders, and (3) woodlots (Lagerlöf et al, 2014;Nyaga et al, 2015). The first two agroforestry systems posed a challenge to be explicitly implemented in SWAT because of the model structure.…”
Section: Simulation Of Agroforestrymentioning
confidence: 99%
“…Practising of intensive agricultural cultivation, as is the case currently in the upper Mara, continually degrades the soil and reduces its capacity to absorb rainwater mainly because of compaction of lower soil horizons, decrease in organic carbon and porosity (Bruijnzeel, 2004;Recha et al, 2012). Trees on the other hand, aid in the recovery of degraded lands Lagerlöf et al, 2014). High organic matter, presence of live and dead roots, increased soil microfauna and enhanced macro-pore flow are some of the factors that improve soil infiltration after establishment of agroforestry Ketema and Yimer, 2014).…”
Section: Impact Of Agroforestry On Catchment Water Balancementioning
confidence: 99%
“…Although previous studies have reported that land-use conversion could alter soil microbial communities [17,18], the mechanisms of the effects of land-use conversion on soil microbial communities are poorly understood. It is commonly believed that the land-useconversion-induced changes in soil physical and chemical properties result in the transformation of soil microbial communities, but no consistent relationships have been observed among various studies.…”
Section: Introductionmentioning
confidence: 99%
“…Otros procesos como la fragmentación física de la broza causada por el viento, la lluvia y las heladas también podrían afectar el proceso de descomposición en ecosistemas áridos y semiáridos (Steinberger et al 1990;Vanderbilt et al 2008). Por otro lado, trabajos realizados en otros ecosistemas con distintos usos de la tierra han encontrado una disminución de la comunidad de microorganismos en los suelos de comunidades vegetales con usos de la tierra más intensos (Lagerlöf et al 2014;Hortal et al 2015;Smith et al 2015). No se puede descartar la posibilidad que, dados los cambios en el ambiente local encontrados en el presente trabajo, se produzca un cambio en la comunidad de microorganismos que pueda relacionarse con la diferencia en la descomposición de los materiales comunes en las configuraciones vegetales.…”
unclassified